Pengaruh Kualitas Sistem, Kualitas Informasi, dan Komitmen Organisasi Terhadap Efektivitas Sistem Informasi Akuntansi: Studi pada PT. Dutaflow Hidrolik - Moulie Cempaka; Dwi Wahyuningsih (MES Management Journal, 2026)
This study aims to analyze the influence of system quality, information quality, and organizational commitment on the effectiveness of accounting information systems (AIS) at PT. Dutaflow Hidrolik. The research employs a quantitative approach with an associative causal design to explain cause-and-effect relationships. Data collection was conducted through questionnaires distributed to employees of PT Dutaflow Hidrolik who have used the Metamorfosys system and have been employed for over a year, excluding the HR team. The sample was determined using the Slovin formula, with 92 respondents required to ensure representative data. However, data from 110 respondents were collected and analyzed. The results indicate that system quality and information quality have a significant positive effect on the effectiveness of AIS. High system quality, characterized by reliability, ease of use, speed, security, and system integration capabilities, supports operational efficiency. Similarly, information quality, marked by accuracy, relevance, completeness, and timeliness, enhances decision-making processes. In contrast, organizational commitment does not significantly affect AIS effectiveness, suggesting that technical factors such as system and information quality play a more critical role. Simultaneously, system quality, information quality, and organizational commitment collectively have a significant effect on AIS effectiveness, as evidenced by an R-squared value of 0.61, indicating that 61% of the variability in AIS effectiveness can be explained by these variables. This study highlights the importance of technical factors in enhancing AIS effectiveness and provides managerial implications for improving system reliability, data accuracy, and employee training to optimize system utilization within the organization.